Inhalation of Orange Peel Aroma: Study on the Effects of Exotic Oils on Blood Pressure Changes - Digna Renny Panduwati; Dian Pratiwi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Oranges are a fruit that is in great demand by the public. Oranges have a sweet taste and distinctive aroma. Orange peel debris is one of the problems that is of concern to the government. This is because there are still many people who do not use it and just throw it away. This is because many people still don't know that orange peel waste contains the active substance d-lemonene. The d-lemonene compound is a compound that has a fragrant and refreshing aroma, so it can provide a calming feeling to those who inhale it. Therefore, this study aims to see the effect of the fragrant aroma of raw orange peel extract on changes in blood pressure. The extraction method used is steam distillation in order to maximize the yield obtained. After obtaining the raw extract, it was characterized using Gas Chromatography Mass Spectrometry (GC-MS) to determine the skin content. The research results showed that the yield of orange peel extract calculated based on the volume of extraction results divided by the sample weight in grams was 20% (v/w). Based on the results of Gas Chromatography Mass Spectrometry (GC-MS) characterization, it shows that the sample contains the compound d-lemonene. The effectiveness test showed a decrease in blood pressure in respondents who had high blood pressure and an increase in pressure in respondents who had low blood pressure. The reason is that the d-lemonene compound contained in orange peel can provide a calming sensation. This can happen because the d-lemonene compound is able to inhibit neuroinflammation and nitrite levels in the hippocampus and relieve anxiety through DAergic and GABAergic nerve activity mediated by A2A receptors.Keywords: Blood Pressure, Essencial Oil, Orange Peel